PENGARUH GREEN MARKETING TERHADAP REPURCHASE INTENTION PADA THE BODY SHOP BANDUNG - Zahra Rahmi Hanifah; Maya Ariyanti (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Currently, the issue of go green is being intensified so that many people are increasingly concerned about the environment, including the concept of green marketing. Cosmetics is one of the businesses that applies the concept of green marketing by making packaging that can be recycled or having products that don't test on animals like The Body Shop does. In mid-2021, The Body Shop uses again green marketing through the Refill Station program. Green perceived quality, green perceived value, and green satisfaction in green marketing affect Repurchase Intention. This study aims to determine the effect of Green Marketing on the Repurchase Intention of The Body Shop Bandung. Quantitative methods are used in research. Green perceived quality, green perceived value, and green satisfaction are independent variables and repurchase intention is the dependent variable. This research uses purposive sampling method by having 400 respondents and collecting data using questionnaire method. The results of this study conclude that green perceived quality, green perceived value and green satisfaction have a significant influence on repurchase intention at The Body Shop Bandung. Green perceived quality, green perceived value and green satisfaction also have a simultaneous influence on repurchase intention at The Body Shop Bandung